Cold water immersion; practices, trends and avenues of effect - McGorm, H.; Roberts, L. A.; Coombes, J. S.; Peake, J. M. (ASPETAR Sports Medicine Journal, 2015)
Cold water immersion and ice baths are popular methods of recovery used by athletes. From the simple wheelie bin with water and ice, to the inflatable baths with complex water cooling units to recovery sessions in the ocean, the practice of cold water immersion is wide and varied. Research into cold water immersion was conducted as early as 1963 when Clarke examined the influence of cold water on performance recovery after a sustained handgrip exercise. Research has been conducted to understand how cold water immersion might affect the body`s physiological systems and how factors such as water temperature and the duration of immersion might enhance recovery after training and/or competition. Despite this research activity, how are we to know if research is being put into practice? In more serious situations, where guidelines and policies need to be standardised for the safe use of a product, one would expect that there is a straight forward follow-on from research into practice. Although cold water immersion may not need the rigor of testing compared to drug treatments, for example, the decision on whether to use cold water immersion in specific situations (e.g. after training or competition) may rest with one or two of the staff associated with the athlete/team. Therefore, it would be expected that these staff are well-informed on the current literature regarding cold water immersion. Cold water immersion; practices, trends and avenues of effect. Available from: https://www.researchgate.net/publication/276145819_Cold_water_immersion_practices_trends_and_avenues_of_effect